Maximum-likelihood estimation of parameters of exponentially damped sinusoids - Parthasarathy, Sarangarajan; Tufts, D. W. (Proceedings of the IEEE, 1985)
Maximum-likelihood estimates of the parameters of exponentially damped sinusoidal signals in noise can be found by using an iterative procedure based on Newton's method. The initial estimate is obtained by an improved linear-prediction method. The properties of the Newton estimates obtained from short data records is experimentally studied.